Making photography matter : a viewer's history from the Civil War to the Great Depression - Finnegan, Cara A. (University of Illinois Press, 2015)
"Photography became a dominant medium in cultural life starting in the late nineteenth century. As it happened, viewers increasingly used their reations to photographs to comment on and debate public issues as vital as war, national identity, and citizenship"--Jacket
Keywords: Documentary photography -- United States -- History -- 20th century.; Documentary photography -- United States -- History -- 19th century.; Photography -- Social aspects -- United States.; Visual Arts.; Art, Architecture & Applied Arts.; Photography.; Photographie documentaire -- États-Unis -- Histoire -- 20e siècle.; Photographie documentaire -- États-Unis -- Histoire -- 19e siècle.; Photographie -- Aspect social -- États-Unis.; COMPUTERS -- Digital Media -- Photography.; PHOTOGRAPHY -- Reference.; TECHNOLOGY & ENGINEERING -- Imaging Systems.; SOCIAL SCIENCE -- Media Studies.; Documentary photography; Photography -- Social aspects; United States; 1800-1999; History